Pathology of Natural Cases of Equine Endocrinopathic Laminitis Associated With Hyperinsulinemia. (September 2015) - Karikoski, N. P.; McGowan, C. M.; Singer, E. R.; Asplin, K. E.; Tulamo, R.-M.; Patterson-Kane, J. C.
Laminitis in equids is a clinical syndrome usually associated with systemic disease. Endocrinopathies recently have been recognized as the most common cause of laminitis, with hyperinsulinemia playing a key role. Descriptions of laminitis-associated lesions have been confusing due to the wide range of experimental models used, failure of adequate clinical documentation for naturally occurring cases, lack of separate analysis of inflammatory and endocrinopathic laminitis, and uncertainty regarding normal morphological variation of lamellae. In this study, lamellar morphology and pathology were described in 14 laminitic horses and ponies that had hyperinsulinemia (>20 mIU/l), with reference to 25 age- and breed-matched controls. The type and severity of lesions noted had no correlation with reported clinical duration and in at least some cases must have preceded it. Lesions were largely localized abaxially within the lamellar tissue and included apoptotic cell death, as well as lamellar fusion, hyperplasia, and partial replacement with aberrant keratin containing nucleated debris and proteinaceous lakes. The lesions resulted in irregular margins between the inner horn and the lamellar tissue. Acute separation originated from the abaxial region, with minimal associated inflammation. Axially, epidermal lamellar tapering was the most frequent morphological observation. The lesions in these chronic cases of laminitis were similar to those described in some inflammatory laminitis models and contained features seen in developmental phases of hyperinsulinemic models. These findings support the theory that repeated episodes of subclinical laminitis occur prior to clinical presentation. In addition, the pathology does not include extensive basement membrane failure seen in some inflammatory models.